Microwave pyrolysis of rice straw to produce biochar as an adsorbent for CO2 capture. (1st May 2015) - Huang, Yu-Fong; Chiueh, Pei-Te; Shih, Chun-Hao; Lo, Shang-Lien; Sun, Liping; Zhong, Yuan; Qiu, Chunsheng
Abstract: The CO2 adsorption on biochar produced by microwave pyrolysis of rice straw was investigated in this study. A microwave power level of 200 W and a maximum temperature of approximately 300 °C would be the optimal parameters to adsorb the most CO2 . The CO2 adsorption capacity was up to 80 mg/g at 20 °C. The adsorption capacity decreased at higher power levels and temperatures possibly owing to the pore destruction. The CO2 adsorption capacity was highly correlated with the specific surface area of biochar. The conventional pyrolysis at 550 °C was optimal to produce the biochar absorbing the most CO2 which, however, was still lower than that of the biochar produced by microwave pyrolysis by about 14%. Low activation energy implies that CO2 adsorption on the biochar is physisorption. The ratio of CO2 quantity versus solid product quantity can almost match the CO2 adsorption capacity of the biochar produced at 200 W microwave power levels, so the microwave pyrolysis without further processes to meet the zero emission of CO2 should be workable. Compared with conventional pyrolysis, microwave pyrolysis could produce the biochar with lower time, cost, and energy consumptions. Highlights: CO2 adsorption capacity of the biochar can be up to 80 mg/g. Optimal parameters for the highest adsorption capacity are 200 W and 300 °C. The biochar adsorbed more CO2 than that produced by conventional pyrolysis by 14%. Microwave pyrolysis can produce biochar with lower time, cost, and energy needs. Zero CO2 emission of microwave pyrolysis can be expectable.